An Evaluation Framework for Communication and Coordination Processes in Offshore Software Development Outsourcing Relationship: Using Fuzzy Methods - Rafiq Ahmad Khan; Mohd Yazid Idris; Siffat Ullah Khan; Muhammad Ilyas; Sikandar Ali; Aziz Ud Din; Ghulam Murtaza; Abdul Wahid Khan; Saeed Ullah Jan (IEEE Access)
Offshore software development outsourcing (OSDO) is a modern business strategy for producing high-quality software at a low cost. The OSDO refers to the practice of contracting to an offshore (extrinsic) organization to perform some or all software development work of a product. For the benefit of the OSDO vendors, this paper aims to develop a “communication and coordination challenges mitigation model” (CCCMM) that provides solutions for unambiguously defined communication and coordination processes in global software development (GSD) environment. Our proposed model is based on the fuzzy multi-attribute decision-making (FMADM) approach incorporating the capability of group decision-making. The FMADM approach is used both in the ranking of survey and assessment of case studies. First, the authors undertook a systematic literature review (SLR) that identified all cited challenges from a set of 101 articles. We identified 18 problem areas faced by the GSD vendors in OSDO relationships. Of these, six were ranked as critical. For the purpose of identifying corrective interventions, a second SLR was conducted that revealed 75 remedial measures extracted from 63 chosen articles. To validate our SLR findings, we surveyed 42 outsourcing experts from six countries. We also categorized six critical challenges and 75 corrective practices into four mitigation levels based on CMMI, SOVRM, and SOPM. In addition, two case studies were conducted to evaluate CCCMM outcomes in OSDO companies. The assessment results of the first case study do not recommend Company-A for the successful implementation of level-2 of the CCCMM, so Company-A stands at level-1. We have observed from the second case study that Company-B has implemented all the critical challenges of the level-2 only; therefore, Company-B is at level-2 “success” of the proposed assessment model.